Principles of law in the legal regulation of social relations in modern conditions: administrative, criminal and constitutional aspects - Basko, Andriy; Hryshyna, Natalia; Obushenko, Nataliia; Fedorov, Ihor; Koteliukh, Mykola (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
The purpose of this paper is to conduct an independent study on the position of legal principles in the legal regulation of public relations in the context of digitalization. In writing this paper, the functional research method was used. The functional research method allows for a thorough clarification of the dynamic aspects of legal principles, their practical objectives, their position and role in the law and in other elements of the legal system of society in general, and their impact on social relations in the form of legal regulation and other forms of legal influence (informational, value-oriented, psychological, system-shaping, etc.). Although the role of legal principles in today's various legal systems is not the same, it is nevertheless concluded that legal principles are one of the sources of law practically everywhere, whether nominal or de facto. The importance of legal principles is that they serve as a framework, the basic structure of the legal system; that they are a guide in the process of development and formation of law; that they have a significant impact on the formation of people's legal consciousness; that they can be a direct basis for making individual legal decisions in a particular case; that they can provide a legislative blanks, reflected in the fact that legal principles can be used as a legal basis for considering legal issues, and that legal principles contribute to the correct interpretation of legal norms while they serve as a source of law.